Hospital Shift Hours and Its Effect on Quality of Life among Nurses: A Comparative Study - Andina Prameswari; Ligina Ayudia; Halimah Sya'diyah; Aulia Iskandarsyah (Universitas Muhammadiyah Semarang, 2021)
In organizing health services in hospitals, the nursing team is the frontline for achieving service for 24 hours continuously, therefore in some division, like ICU or ER, nurses work with shift hours. There is some evidence of shift work’s psychological and physiological effects that can influence nurses' quality of life. This study aims to obtain an overview of the quality of life in nurses who work into the shift and its comparison with non-shift. This study was an online survey that involving nurses from hospital-based in Bandung. The survey was distributed online, where participants who participated in the survey had certain criteria. Data collection carried out with questionnaires from WHOQOL-BREF, designed using a cross-sectional comparative study model. Forty-five nurses were included in this study with 82% are woman, with 77,7% work with shift and 22,2% no-shift. Overall, the quality of life of nurses works in shift decreased in the physical domain. Specifically, those who perceived themselves had physical pain. Even so, they still perceived good quality of sleep. Nurses work in shift also perceived negative emotion such as feeling blue, anxiety and depression. There were two differences between nurse with shift work and non-shift work in quality of life domains (physical, U= 83,5, p-value= 0,012) and (environment, U= 102,5, p-value= 0,047). Physical pain, less free time to relax, and physical activity such as exercising may influence the lower quality of life. Nurses with shift work and nurses with non-shift work also found significantly different in their overall health (U=84, p-value=0,008). It might be related to how they perceived their health issue.